From Solid Evolution to Liquid Evolution: Challenges to Public Administration and Institutions - Rautakivi, Tuomo; Yolles, Maurice (KnE Social Sciences, 2023)
This paper aims to explain some forms of development and the relationship between development adaptations. Development has a cultural perspective, and culture can be explored in terms of the relationship between institutional values and norms. Changes in internal and external climate affect and challenge prevailing culture, which includes values, beliefs, and norms. These changes (socio-cultural) have an impact on the social meaning, norms, and development of society. Development within a socio-political context is defined in terms of institutional processes, enabling a wide class of complex situations to be addressed. Development is an adaptive attribute of a changing socio-political agency with interactive ties to its environment. It is connected to globalization, which is part of that environment, as the global COVID-19 pandemic or Ukraine war clearly shows. The period of change creates instability and cultural uncertainty because values may become confused, and so, sociocultural processes may become a liquid society. The changes challenge public administration, public policy, and their capacity to answer changing situations. This study uses Bauman’s idea of a liquid society and Yolles’ Cultural Agency Theory (CAT). A political agent will be generically modeled using CAT, and the neo-institutional processes and their capacity for development will be explored. Keywords: liquid evolution, uncertainty, sensate, Ideational, populism